All The Pretty Pictures. - Hoffmann, Leah (Communications of the ACM, 2017)
An interview is presented with the computer scientist and 2016 ACM Prize in Computing recipient Alexei Efros. When asked about his early influences in computer science (CS), he mentions reading on PDP-11 assembly language programming as a child. He comments on his work in computer graphics, including in regard to the behavior of light. When asked about his research on examining data and images from the web resource Flickr, he discusses the use of neural networks.